PTU-132 The changing platform of small bowel endoscopy: a 15-year experience of demand and outcomes. (17th June 2017) - Zammit, S Chetcuti; Ching, H-L; McAlindon, ME; Sanders, DS; Healy, A; Thurston, V; Sidhu, R
Abstract : Introduction: The development of capsule endoscopy (CE) and enteroscopy have increased the ability to investigate and treat pathology in the small bowel. We have been providing a comprehensive small bowel endoscopy service and we present our data from the last 15 years evaluating demand, diagnostic yield and impact on patient management. Method: A retrospective analysis was conducted on patients who underwent CE, push enteroscopy (PE), double balloon enteroscopy (DBE) and intraoperative enteroscopy (IOE) between January 2002 and December 2016. Results: A total of 5065 CEs, 569 DBEs, 327 PEs and 22 IOEs were performed over 168 months. Obscure gastrointestinal bleeding (OGB) and anaemia were the most common indications for CE (37.8%), DBE (30%) and IOE (55%). Exclusion of coeliac disease complications (26.6%) was the most common indication for PE. The majority of patients had a CE prior to DBE (83.4%) and IOE (81.8%) (p=0.0001). Fifty percent of patients had a DBE prior to IOE. The demand for CE has plateaued over the past few years compared to the demand for DBE which is rising. The demand for PE has fallen dramatically (p=0.0001). This is also true for IOE and its use is reserved only for lesions beyond the limits of DBE (p=0.0001). In 2016, for every 11 CE s performed, 1 patient underwent a DBE locally. The diagnostic yield for CE, PE, DBE and IOE were 29%, 43.9%, 53.8% and 89.5% respectively (p=0.0001). The diagnostic yield for CE has fallen over the years (p=0.0001). This is perhaps due to the lower threshold for performing CE by the referring clinicians. The diagnostic yield for CE was highest for the indication of OGB (36%) compared to Crohn's disease (30.0%, p=0.001). This contrasts with the diagnostic yield of DBE which has risen gradually (p=0.0001). Fifteen percent of patients underwent a DBE despite a negative CE. The yield for DBE in this group of patients was only 4.3% (p=0.0001). The rate of therapeutics for DBE, PE and IOE were 29%, 20% and 77% respectively. The majority of therapeutic procedures performed were argon plasma coagulation to angioectasias and polypectomies. The complication rates were 2% for DBE, 0.9% for PE and 13.6% for IOE (p=0.004). Complications following DBE included cardiovascular events (0.2%), respiratory compromise (0.9%), pancreatitis (0.2%) and gastrointestinal bleeding following polypectomy in (0.2%). Conclusion: This is one of the largest series to date comparing the clinical utility and yield of all 4 small bowel endoscopic modalities. Enteroscopy has an important role in providing further management directed by CE. In patients with a negative CE, the yield of DBE is low, hence careful patient selection is required to maximise the use of resources. Disclosure of Interest: None Declared